Autoignition of ethanol-diesel blends: Is it worth dehydrating ethanol?. (1st June 2022) - Cova-Bonillo, Alexis; Patiño-Camino, Rayda; Hernández, Juan José; Lapuerta, Magín
Highlights: Higher ethanol content leads to longer ignition delay and slower combustion speed. For low ethanol content, autoignition time increases for hydrated ethanol. For high ethanol content, autoignition time decreases with water content. The collisional effect of water can compensate the effect of evaporation cooling. As far as miscibility is guaranteed, dehydration is not essential for autoignition. Abstract: This study analyses the impact of the concentration of water in ethanol on the autoignition characteristics of ethanol-diesel blends. A constant volume combustion chamber was used to emulate the conditions of a diesel engine. Tests were carried out modifying the water content in the alcohol, and then the concentration of hydrated ethanol in the diesel fuel, at an initial temperature of 650 °C and 535 °C and pressure of 21 bar. The results reveal that, in general, the presence of water in alcohol, at concentrations requiring no additives to assure miscibility, has little effect on autoignition times. It was found that at low hydrated ethanol contents water acts as a reactivity inhibitor, probably associated with the endothermic effect of evaporation of the injection liquid. However, at higher concentrations of hydrated ethanol, water acts as an autoignition enhancer. Simulations suggest that the chemical effect associated with water as a third-body becomes more important compared to other effects. Finally, from an autoignition standpoint, exhaustive dehydration of ethanol is perhaps not necessary, which would open a market niche to hydrated ethanol derived from industry wastes or surplus.